Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/1744-7917.12630
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore‐induced rice resistance against rice blast mediated by salicylic acid

Abstract: In agro-ecosystems, plants are important mediators of interactions between their associated herbivorous insects and microbes, and any change in plants induced by one species may lead to cascading effects on interactions with other species. Often, such effects are regulated by phytohormones such as jasmonic acid (JA) and salicylic acid (SA). Here, we investigated the tripartite interactions among rice plants, three insect herbivores (Chilo suppressalis, Cnaphalocrocis medinalis or Nilaparvata lugens), and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In turn, application of MeJA and JA on rice plants activates diverse defense metabolites, including polyphenol oxidase, TrypPI, and plant volatiles, thereby leading to the direct and indirect resistance of plants to herbivores [ 14 , 42 , 43 ]. Previously, it has been shown that C. medinalis infestation suppresses the endogenous SA in rice plants [ 18 ]. Our results, together with those of previous reports, suggested that an antagonistic interaction of JA and SA might be involved in rice defense against C. medinalis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, application of MeJA and JA on rice plants activates diverse defense metabolites, including polyphenol oxidase, TrypPI, and plant volatiles, thereby leading to the direct and indirect resistance of plants to herbivores [ 14 , 42 , 43 ]. Previously, it has been shown that C. medinalis infestation suppresses the endogenous SA in rice plants [ 18 ]. Our results, together with those of previous reports, suggested that an antagonistic interaction of JA and SA might be involved in rice defense against C. medinalis .…”
Section: Discussionmentioning
confidence: 99%
“…A soft brush was used to place one 3rd-instar C. medinalis on the second leaf from the top. The larvae were starved for 2 h before experiments and confined within a small Parafilm bag [ 18 ]. For the time-course bioassays, the larvae were transferred to rice leaves for the final 1, 6, 12, or 24 h of the experiment ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Bemisia tabaci adults and nymphs both damage plants, but they all induce the SA pathway by suppressing the JA pathway (Zhang et al ., 2013; Zhang et al ., 2015; Zhang et al ., 2018a). In addition, only caterpillar larvae of Cnaphalocrocis medinalis and Chilo suppressalis cause damage to plants; these larvae activate the JA pathway but reduce or have no effect on the SA pathway (Zhang et al ., 2020). We hypothesize that this difference is due to different crosstalk interactions between JA and SA, with a positive crosstalk interaction between JA and SA possibly occurring in leafminer larva‐fed plants.…”
Section: Discussionmentioning
confidence: 99%
“…This has been well-attributed to pre and post herbivory attacks in plants [17][18][19] . Besides, SA has also been coined for its resilient role in enhancing resistance against insect induced pathogenic attacks 35 . The current results showed that JA and SA contents were not antagonistic to each other and both were higher as compared to control.…”
Section: Discussionmentioning
confidence: 99%